PENERAPAN PERATURAN MAHKAMAH KONSTITUSI NOMOR 1 TAHUN 2023 TENTANG MAJELIS KEHORMATAN MAHKAMAH KONSTITUSI DALAM PUTUSAN MKMK NOMOR: 2/MKMK/L/11/2023 - Mene, Meydianto (Ensiklopedia Education Review, 2023)
MKMK decision Number 2/MKMK/L/11/2023 does not refer to PMK No. 1 of 2023 concerning the Honorary Council of the Constitutional Court, the only sanction for serious violations is dishonorable dismissal and there are no other sanctions as regulated in Article 41 letter c and Article 47 of Constitutional Court Regulation Number 1 of 2023 concerning the Honorary Council of the Constitutional Court. This research is descriptive in nature, namely an attempt to describe the Constitutional Court Regulation Number 1 of 2023 concerning the Honorary Council of the Constitutional Court in the MKMK Decision Number: 2/MKMK/L/11/2023.Keywords: Regulations, Constitutional Court, Honorary Council of the Constitutional Court.